The effect of composition of a polymeric coating on the biofilm formation of bacteria and filamentous fungi - Mikusova, Nikola; Nechvílová, Kateřina; Kalendová, Andréa; Hájková, Tereza; Capakova, Zdenka; Junkar, Ita; Lehocky, Marian; Mozetic, Miran; Humpolicek, Petr (Taylor and Francis, 2019)
Functionality of polymeric coating, especially in terms of anti-corrosive properties and stability, can be negatively influenced by formation of either bacterial or fungal biofilm on its surface. Herein, the epoxy-ester resin based polymeric coating was filled with pigments (natural silicon dioxide diatomite, natural wollastonite, tungstate and molybdate). Pigments was modified by conducting polymers (polyaniline phosphate, polypyrrole phosphate, poly(p-phenylenediamine) phosphate and ZnFe2O4). Impact of modified pigments on the surface energy and formation of biofilm were tested. The use of various biofilm forming species of both the bacteria and fungi filled a knowledge gap about their behavior on polymeric coatings. [GRAPHICS] .
Vliv složení polymerního povlaku na tvorbu biofilmu bakterií a vláknitých hub
Keywords: Bacteria; biofilm formation; fungi; pigment; polymeric coating; bakterie; tvorba biofilmu; houba; pigment; polymerní povlak